THE CORRELATION OF PHARMACEUTICAL SERVICES TO THE LEVEL OF SATISFACTION WITH COVID-19 VACCINATION PARTICIPANTS IN RS TINGKAT II UDAYANA - Iwan Saka Nugraha; Wahyuni W Udi (Journal Pharmaceutical Science and Application, 2022)
Background: The obligation to vaccinate against Covid-19 in an effort to prevent national COVID transmission is contained in Presidential Regulation No.99 of 2020. Healthy, safe and quality COVID-19 vaccination services can be realized with pharmaceutical services. Objective: This research aims to study the correlation of pharmaceutical services to the level of satisfaction after the covid-19 vaccination at RS Tingkat II Udayana. Methods: The research design was a Cross-Sectional study which used an analytical survey. The population in the study was all participants of the COVID-19 vaccine in June at RS Tingkat II Udayana, which consisted of 500 participants. The sample in this study was obtained by using the total sampling method. Data collection in this study used primary data. Data analysis is carried out univariately and bivariate. Results: The results of the study found that vaccination participants were satisfied with pharmaceutical services, as shown from the comparison of services received and patient expectations. There is a relationship between pharmaceutical services, variables of guarantee, empathy, and physical evidence to the satisfaction of COVID vaccination participants at RS Tingkat II Udayana. Conclusions: variables of guarantee, empathy, and physical evidence have a significant correlation with the satisfaction of vaccination participants. Keywords: Pharmaceutical Services; Satisfaction; Vaccination